Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.3600
|View full text |Cite
|
Sign up to set email alerts
|

FRI0738-HPR Nurse-led screening: changes in cardiovascular risk profile and association to socio-economic status in outpatients with inflammatory arthritis

Abstract: Background:Persons with inflammatory arthritis have an increased risk for cardio-vascular (CV) disease and screening is therefore recommended (1)Objectives:To investigate changes in the patient’s risk for CV disease and whether risk reduction was associated with socio-economic status in a hospital population of outpatients with inflammatory arthritis (IA) (rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS))Methods:Outpatients with IA ≤85 years of age connected to King Christia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similar statements were found in this study, where the participants described improvement in their overall well-being following an increase in physical activity. A previous study explored changes between the first and second screening in patients with inflammatory arthritis [ 35 ]. The study found that 18% of the patients at high risk and 20% of the patients at low risk increased their physical activity from <5 to ≥5 times a week [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar statements were found in this study, where the participants described improvement in their overall well-being following an increase in physical activity. A previous study explored changes between the first and second screening in patients with inflammatory arthritis [ 35 ]. The study found that 18% of the patients at high risk and 20% of the patients at low risk increased their physical activity from <5 to ≥5 times a week [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study explored changes between the first and second screening in patients with inflammatory arthritis [ 35 ]. The study found that 18% of the patients at high risk and 20% of the patients at low risk increased their physical activity from <5 to ≥5 times a week [ 35 ]. The study also explored changes in smoking habits and found that 20% of high-risk patients and 15% of low-risk patients, who had reported being smokers at the initial screening, had transitioned to non-smokers by the second screening [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation